Rapid Patient-Side Evaluation of Endothelial Glycocalyx Thickness in Healthy Sedated Cats Using GlycoCheck® Software - Yozova, Ivayla D.; Londoño, Leonel A.; Millar, Kristina K.; Sano, Hiroki; Weidgraaf, Karin; Thomson, Neroli A.; Munday, John S. (Frontiers in Veterinary Science, 2022)
The endothelial glycocalyx (EG) determines transvascular fluid fluxes, and influences inflammation, coagulation, and capillary blood flow. The GlycoCheck® software calculates EG thickness using sidestream dark field videomicroscopy recordings. This method has not been evaluated for use in cats. The aim of the present study was to evaluate the use of GlycoCheck® for estimating EG thickness in healthy cats, and to investigate the variability of EG thickness in this population. One hundred and one healthy research-purposed cats were included in the study. The cats were sedated, and a handheld videomicroscope, connected to GlycoCheck® software, was used to evaluate the sublingual microvasculature. The parameters measured included perfused boundary region (PBR, an indirect measurement of EG thickness) in vessels between 5 and 25 µm in diameter, valid vessel density, percentage red blood cell filling, and median red blood cell column. Heart rate, respiratory rate, pulse oximetry and oscillometric blood pressure readings were also recorded. There were 35 neutered male cats, 11 intact males, 38 neutered females, and 17 intact females. The average age was 63 months (range, 11–160 months). Tolerance intervals for PBR were 1.89 – 3.00 µm (95% CI, lower limit 1.76 – 2.04, upper limit 2.83 – 3.13 µm); for valid vessel density were 73.33 – 333.33 µm/mm2 (95% CI, lower limit 77 – 99.33, upper limit 312.67 – 350.33 µm/mm2); for red blood cell filling percentage were 59.85 – 85.07% (95% CI, lower limit 58.97 – 63.33, upper limit 83.07 – 88.20 %); and for median red blood cell column width were 5.63 - 8.59 µm (95% CI, lower limit 5.28 – 6.07, upper limit 8.14 – 9.51 µm). There was a negative association between median red blood cell column width and body weight (p = 0.007). The median red blood cell column was significantly wider in intact females when compared to spayed females (p = 0.033). The GlycoCheck® analysis was easily performed in healthy sedated cats. Clinical variables did not have an effect on EG thickness. These results suggest that this technique could be valuable for evaluation of the EG and microvascular parameters in cats.